Internet use and attitude toward aging among Chinese older adults: the mediating role of health - Xuehui Wang (Frontiers in Public Health)
ObjectivesThis research seeks to explore the relationship between Internet use and attitudes toward aging among older adults in China, with a particular emphasis on the mediating role of health in this correlation.MethodsA national survey of 10,858 Chinese adults aged 60 and above was conducted, employing multiple linear regression and structural equation modeling to analyze the impact of Internet use on aging attitudes with health as a mediator.ResultsThe research found a significant positive association between Internet use and positive aging attitudes (β = −1.420, p < 0.001). Health indicators—self-rated, physical, and mental health—were identified as key moderators, with healthier adults benefiting more from Internet use.ConclusionThis research reveals a positive association between Internet use and attitudes toward aging among older adults in China. These findings hold substantial implications for encouraging active and healthy aging in the digital era, underscoring the value of advocating for digital engagement among seniors as a means to improve their quality of life.